Biofertilizers: A Sustainable Approach to Enhance Rice Cultivation - Ankireddypalli, Jaya Kishore; Ankela, Charan Babu; Naik, M. Ramesh; Teja, R. Ravi (Chronicle of Bioresource Management, 2020)
Rice is a staple food for nearly half of the global population, yet conventional farming practices rely heavily on chemical fertilizers, leading to soil degradation, water pollution, and environmental concerns. As the demand for sustainable agriculture grows, biofertilizers have emerged as an eco-friendly alternative, enhancing soil fertility and promoting plant growth through beneficial microorganisms. Biofertilizers, including nitrogen-fixing bacteria (e.g., Rhizobium, Azospirillum), phosphate-solubilizing microorganisms (e.g., Pseudomonas, Aspergillus), and plant growth-promoting rhizobacteria (PGPR), play a crucial role in nutrient availability and soil health. Their application in rice cultivation reduces dependency on synthetic fertilizers, improves crop resilience to environmental stress, and supports long-term agricultural productivity. Furthermore, biofertilizers contribute to global sustainability goals (SDGs), such as climate action (SDG 13) and food security (SDG 2), by reducing greenhouse gas emissions and enhancing yield stability. As concerns over chemical-based agriculture rise, biofertilizers present a promising solution for sustainable rice farming, ensuring environmental protection while maintaining food security for future generations.